2015
DOI: 10.1017/s1751731114003012
|View full text |Cite
|
Sign up to set email alerts
|

The use of genetic engineering techniques to improve the lipid composition in meat, milk and fish products: a review

Abstract: The health-promoting properties of dietary long-chain n-3 polyunsaturated fatty acids (n-3 LCPUFAs) for humans are well-known. Products of animal-origin enriched with n-3 LCPUFAs can be a good example of functional food, that is food that besides traditionally understood nutritional value may have a beneficial influence on the metabolism and health of consumers, thus reducing the risk of various lifestyle diseases such as atherosclerosis and coronary artery disease. The traditional method of enriching meat, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Similarly, use of citric acid found to increase retention of phosphorus (Brenes et al, 2003), tibia ash (Rafacz-Livingston et al, 2005;Martinez-Amezcua et al, 2006;Moghadam et al2006), and toe ash (Atapattu and Nelligaswatta, 2005) in broiler chicks. In a recent study, Świątkiewicz and Arczewska-Wlosek (2012) reported that organic acids have no effects on increases the solubility and absorption of phosphorus and calcium in the small intestine (Overland et al, 2002), thereby improving retention of phosphorus and calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, use of citric acid found to increase retention of phosphorus (Brenes et al, 2003), tibia ash (Rafacz-Livingston et al, 2005;Martinez-Amezcua et al, 2006;Moghadam et al2006), and toe ash (Atapattu and Nelligaswatta, 2005) in broiler chicks. In a recent study, Świątkiewicz and Arczewska-Wlosek (2012) reported that organic acids have no effects on increases the solubility and absorption of phosphorus and calcium in the small intestine (Overland et al, 2002), thereby improving retention of phosphorus and calcium.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with other reports in laying hens, that CB enhanced feed efficiency (Xiang et al, 2019;Wang et al, 2020), while synbiotics enhanced feed intake (Tang et al, 2017). The positive effects of diets on laying performance, egg mass and feed efficiency could be attributable to availability of nutrients necessary for metabolism, maintenance and egg production (Markowiak and Śliżewska, 2018), probably because probiotics and prebiotics modulate gut structure for efficient nutrient absorption (Swiatkiewicz et al, 2015;Tang et al, 2017;Xiang et al, 2019). Also, gut fermentation effects are linked with production of short-chain fatty acids which nourish the enterocytes, protect the villi from pathogen invasion and invariably increase microvilli structures for nutrient absorption (Hajiaghapour and Rezaeipour, 2018;Liu et al, 2018).…”
Section: Laying Performance and Egg Qualitymentioning
confidence: 99%